Sentinel lymph node biopsy guideline concordance in melanoma: Analysis of the National Cancer Database. Issue 4 (9th June 2021) - Narang, Jatin; Hue, Jonathan J.; Bingmer, Katherine; Hardacre, Jeffrey M.; Winter, Jordan M.; Ocuin, Lee M.; Ammori, John B.; Mangla, Ankit; Bordeaux, Jeremy; Rothermel, Luke D.
Abstract: Background and Objectives: This study investigated the impact of treating facility type on guideline‐concordant sentinel lymph node biopsy (SLNB) management in T1a* (defined as a Breslow depth <0.76 mm without ulceration or mitoses) and T2/T3 melanoma. Methods: This was a retrospective cohort study utilizing the National Cancer Database from 2012 to 2016. Results: Our cohort included 109, 432 patients. For T1a* melanomas, 85% of patients received guideline‐concordant SLNB management at community and academic facilities versus 75% of patients at integrated network facilities ( p  < .001). Over 83% of patients with T2/T3 melanoma treated at an academic facility received guideline‐concordant SLNB management versus 77% treated at a community facility ( p  < .001). Adjusting for demographic and clinical factors, integrated (adjusted odds ratio, aOR = 0.54), and comprehensive community (aOR = 0.74) facilities were less likely to provide guideline‐concordant SLNB management in patients with T1a* melanoma compared to academic facilities. Community facilities (aOR = 0.72) were less likely to provide guideline‐concordant SLNB management in patients with T2/T3 melanoma compared to academic facilities. Conclusion: Academic facilities provide the highest rate of guideline‐concordant sentinel lymph node management. Comparatively, community programs may underutilize SLNB in T2/T3 disease, while integrated and comprehensive community facilities may over‐utilize SLNB in T1a* disease.